Infectious spleen and kidney necrosis virus‐associated large‐scale mortality in farmed giant gourami, Osphronemus goramy, in India. Issue 12 (27th August 2021) - Swaminathan, Thangaraj Raja; Raj, Nithianantham Sundar; Preena, Prasannan Geetha; Pradhan, Pravata Kumar; Sood, Neeraj; Kumar, Rahul Girish; Sudhagar, Arun; Sood, Naresh Kumar
Abstract: Megalocytivirus cause diseases that have serious economic impacts on aquaculture, mainly in East and South‐East Asia. Five primary genotypes are known: infectious spleen and kidney necrosis virus (ISKNV), red sea bream iridovirus (RSIV), turbot reddish body iridovirus (TRBIV), threespine stickleback iridovirus (TSIV) and scale drop disease virus (SDDV). ISKNV‐mediated infectious spleen and kidney necrosis disease (ISKND) is a major viral disease in both freshwater and marine fish species. In this study, we report the isolation of ISKNV from diseased giant gourami, Osphronemus goramy, in India. Transmission electron microscopy of ultrathin sections of kidney and spleen revealed the presence of numerous polygonal naked viral particles having an outer nucleocapsid layer within the cytoplasm of enlarged cells (115–125 nm). Molecular and phylogenetic analyses confirmed the presence of ISKNV and the major capsid protein (MCP) (1, 362 bp) gene in the infected fish had a high similarity to the other ISKNV‐I isolates. Moreover, ISKNV was propagated in the Astronotus ocellatus fin (AOF) cell line and further confirmed genotypically. A high mortality rate (60%) was observed in gourami fish injected with ISKNV‐positive tissue homogenate through challenge studies. Considering the lethal nature of ISKNV, the present study spotlights the implementation of stringent biosecurity practices for the proper control of the disease in the country.